Fluxus. - Hendricks, Jon; Kellein, Thomas; Kunsthalle Basel (Basel : Kunsthalle Basel, 1994)
Andersen, Eric ; AY-O ; Ben ; Beuys, Joseph ; Brecht, George ; Corner, Philip ; Dufrêne, François ; Filliou, Robert ; Flynt, Henry ; Hi Red Center ; Higgins, Dick ; Ichiyanagi Toshi ; Jones, Joe ; Knowles, Alison ; Koepcke, Arthur ; Kosugi, Takehisa ; Kubota, Shigeko ; Maciunas, George ; Moore, Peter ; Oldenburg, Claes ; Ono, Yoko ; Paik, Nam June ; Patterson, Benjamin ; Riddle, James ; Saito, Takako ; Schmit, Tomas ; Shiomi, Mieko (Chieko) ; Spoerri, Daniel ; Tone Yasunao ; Topor, Roland ; Vostell, Wolf ; Watts, Robert ; Williams, Emmett ; Young, La Monte
bibliog. fluxus p. 139-142
Duits
Fluxus, Kunsthalle Basel, 21. Augustbis 31. Oktober 1994
boek